Voyeurism, Anxiety, and the Persistence of Trauma: Diversifying Film Noir in European Cinema (KULT_online, 2011)
Following up on his 2002 book Film Noir—considered mandatory reading for every student of Hollywood cinema—Andrew Spicer impresses his readers with European Film Noir, a wide-ranging collection of essays by internationally renowned film scholars. The volume is as enlightening as it is accessible, mapping out a territory of films that are usually obscured by their more famous American counterparts. The book’s significance to the field of film studies is twofold. Not only do the essays in this volume carve out the distinctive noir strains in French, British, German, Spanish and Italian cinemas, they also advance an updated understanding of film noir as both a cinematic legacy and an idea that critics have projected onto the past. One of the book’s most compelling insights concerns the fact that European film noir was largely shaped by a common need to work through the traumatic experience of war.